Observed joint infection incidence following needle arthroscopy performed in operating and nonoperating room environments in client-owned dogs: A retrospective cohort study - Alessandra Chiaramonte; Cassio R. A. Ferrigno; Darryl L. Millis; Jessica W. Montoya (PLoS ONE, 2026)
Objective To report the use of needle arthroscopy (NA) on an outpatient basis and to compare joint infection rates following needle arthroscopy performed under general anesthesia in an operating room (OR) versus heavy sedation in a nonoperating room (NOR) clinical environment in client-owned dogs. We hypothesized that there would be no observed increase in infection risk dependent on location in this cohort. Study design A retrospective study of 75 dogs, inclusive of 90 individual joints, that underwent needle arthroscopy at one academic institution from May 4 th , 2022, through December 20 th , 2024. A consent form authorizing the use of medical information for clinical research was obtained for every dog undergoing treatment upon admission to the hospital. Results After excluding for pre-existing infection, fifty-six joint NA (45 dogs) were performed in an operating room under general anesthesia, while thirty-four joint NA (30 dogs) were performed under heavy sedation in a nonoperating room environment. Routine follow-up was collected either in clinic or by referring veterinarian examinations for NA OR (57.8 ± 0.87 days, range 7–365 days) and NA NOR (42.6 ± 1 day, range 7–425 days). One case in the OR group was lost to follow-up. No inferential statistical analysis was performed due to no observed infections in either treatment group. Conclusion In this cohort, no postoperative joint infections were observed following outpatient needle arthroscopy performed under heavy sedation when appropriate aseptic technique was used.